EDUKASI PENGELOLAAN SAMPAH ORGANIK MENJADI ECO-ENZYM PADA IBU RUMAH TANGGA DI WILAYAH KERJA PUSKESMAS GARUDA - Betty Nia Rulen; Lia Fentia; Zurni Seprina; Ratna Juwita (Ensiklopedia Research and Community Service Review, 2025)
Waste management, particularly of organic waste from food residues (food waste), has become an increasingly pressing environmental issue in urban areas such as Pekanbaru City. Tangkerang Barat Sub-district, characterized by high population density and numerous Food Processing Places (TPM), is one of the hotspots for organic waste accumulation. This community service program aimed to enhance the knowledge and skills of housewives in managing household organic waste by converting it into eco-enzyme, a low-cost and environmentally friendly solution that is simple to implement. The activities included socialization, training on waste segregation, and hands-on practice in producing eco-enzyme using vegetable and fruit scraps. The fermentation process of eco-enzyme was explained in detail to ensure participants could replicate it independently. Evaluation results indicated that 75% of participants were willing to apply eco-enzyme production at home, and all participants acknowledged the benefits of the training. This initiative is expected to foster a more sustainable and community-based household waste management system. Keywords: organic waste, eco-enzyme, household waste